2016
DOI: 10.1038/srep35308
|View full text |Cite|
|
Sign up to set email alerts
|

Protein tyrosine phosphatase 1B targets PITX1/p120RasGAP thus showing therapeutic potential in colorectal carcinoma

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is known to promote the pathogenesis of diabetes and obesity by negatively regulating insulin and leptin pathways, but its role associated with colon carcinogenesis is still under debate. In this study, we demonstrated the oncogenic role of PTP1B in promoting colon carcinogenesis and predicting worse clinical outcomes in CRC patients. By co-immunoprecipitation, we showed that PITX1 was a novel substrate of PTP1B. Through direct dephosphorylation at Y160, Y175 and Y179, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…[ 21 ] PTP1B induces down-regulation of paired like homeodomain expression by acting on phospho(Y)-paired like homeodomain in colorectal carcinoma. [ 22 ] PTP1B promotes the proliferation and metastasis of cells via inducing src and extracellular regulated protein kinases activation in non-small cell lung cancer. [ 23 ] In contrast, it was reported that PTP1B degraded by CAPN1 (calpain) promoted malignant behavior and erlotinib resistance of lung adenocarcinoma through phosphorylating cellular-mesenchymal epithelial transition factor and phosphoinositide-3-kinase regulatory subunit 2.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] PTP1B induces down-regulation of paired like homeodomain expression by acting on phospho(Y)-paired like homeodomain in colorectal carcinoma. [ 22 ] PTP1B promotes the proliferation and metastasis of cells via inducing src and extracellular regulated protein kinases activation in non-small cell lung cancer. [ 23 ] In contrast, it was reported that PTP1B degraded by CAPN1 (calpain) promoted malignant behavior and erlotinib resistance of lung adenocarcinoma through phosphorylating cellular-mesenchymal epithelial transition factor and phosphoinositide-3-kinase regulatory subunit 2.…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal squamous cell carcinoma, PTP1B promotes cell invasion and migration by dephosphorylating MYH9 at Y1408, which results in increased EGFR expression [27]. In colorectal carcinoma, PTP1B directly dephosphorylates PITX1 at Y160, Y175 and Y179, which destabilizes PITX1 and consequently results in downregulation of the PITX1/p120RasGAP axis [28]. However, the biological function of PTP1B in MM is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of PITX1 by sorafenib treatment resulted in inhibition of RAS activity in hepatocellular carcinoma (HCC) cell lines. Additionally, inhibition of PTP1B phosphatase activity was accompanied by up-regulation of PITX1 expression in colon cancer cell lines by the receptor tyrosine kinase inhibitor regorafenib 36 . The Expression Atlas web tool showed that PTP1B expression is positive in melanoma cell lines as well as in colon and HCC cell lines ( https://www.ebi.ac.uk/gxa/home ).…”
Section: Discussionmentioning
confidence: 99%